Forage yield of some grasses in monoculture and their mixtures with legumes under irrigation in central Sudan - Sid Ahmed, Nasreldein; Gangi, A.S.; Ibrahim, A.E.S.; Mohamed, I.E. (المجلة الزراعية; مجلد 15 عدد 2 (2017), 2017)
Mixed cropping system provides forage of higher yield than monoculture. This study was conducted during autumn, summer and winter seasons of 2014/15 and 2015/16 at the experimental farm of the Faculty of Agricultural Sciences, University of Gezira, Wad Medani, Sudan. The objective of this study was to investigate the effects of monoculture of selected grasses and their mixtures with selected legumes on their fresh forage yield under irrigation in central Sudan. The experimental material consisted of three grasses, namely; Sudan grass (SG), maize (MZ) and Abu70 and three legumes, cowpea (CP), black-eyed bean (BB) and lablab bean (LB). Grasses were grown in pure stand or mixed with legumes in 1:1 and 2:1 ratios. The results showed that mixing significantly increased growth parameters during all seasons. The highest fresh forage yield of grasses was obtained by the mixture compared with monocultures. Land equivalent ratio exceeded 1.0 in all seasons which indicated clearly the advantage of mixtures over monocultures. Based on the results of this study, to obtain high forage yield of grasses, it was recommended to use seed combinations of 40 kg/ha MZ + 20 kg /ha LB, 40 kg /ha SG+ 20 kg /ha CP and 40 kg /ha SG + 20 kg /ha LB during autumn, summer and winter seasons, respectively.       يؤدي الخلط إلى زيادة في إنتاجية العلف. أجريت هذه الدراسة خلال صيف و خريف وشتاء 2014/15 و2015/16 بالمزرعة التجريبية، كلية العلوم الزراعية، جامعة الجزيرة، السودان. تهدف هذه الدراسة لتقييم أثر الخلط علي إنتاجية العلف لبعض الحشائش النجيلية ومخاليطها بالبقوليات تحت ظروف الري في أواسط السودان. تضمنت الدراسة ثلاثة محاصيل نجيلية هي حشيشة السودان وأبوسبعين والذرة الشامية وثلاثة محاصيل بقولية هي اللوبيا الحلو واللوبيا البيضاء واللوبيا العفن. زرعت المحاصيل النجيلية منفرده وفي مخاليط بنسبة  1:1و1:2 أظهرت نتائج التحليل أن كل من الإنتاج ومكوناته قد زادت زيادة معنوية كنتاج للخلط. تحققت الإنتاجية العالية للعلف الأخضر عند زراعة الاعلاف النجيلية في مخاليط مقارنة بزراعتها منفرده. قيم نسبة مكافئ الأرض فاقت الواحد الصحيح (1.0) خلال كافة المواسم مما يؤكد تفوق نظام الخلط علي زراعة المحصول نقيا. بناء علي نتائج هذه الدراسة ولتحقيق إنتاجية أعلاف نجيلية عالية نوصي بزراعتها في مخاليط بنسبة 40 كجم بذور/هكتار ذرة شامية + 20 كجم بذور/هكتار لوبيا عفن و 40 كجم بذور/هكتار حشيشة السودان + 20 كجم بذور/هكتار لوبيا حلو و 40 كجم بذور/هكتار حشيشة السودان + 20 كجم بذور/هكتار لوبيا عفن خلال مواسم الخريف والصيف والشتاء على التوالي.